A Pictorial Review of Sonography of Intramammary Lymph Nodes: When to Care and What to Do About It. Issue 1 (March 2019) - Hudspeth, Tessa N.; Shin, Kyungmin; Babiera, Gildy V.; Krishnamurthy, Savitri; Woodtichartpreecha, Piyanoot; Karbasian, Niloofar; Whitman, Gary J.
Abstract : Abstract: This pictorial essay reviews and illustrates benign and malignant features of intramammary lymph nodes on mammography, ultrasound, and magnetic resonance imaging, including a review of the clinical and the prognostic significance in patients with known breast cancer. This pictorial essay discusses management suggestions for intramammary lymph nodes in patients with breast cancer.